Computational Probe on Hydrogen Bonding Interaction of Some Aliphatic Alcohol and Water - Mrinal J. Bezbaruah; Bipul Bezbaruah (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
Hydrogen bonding interactions in low molecular weight alcohols or lower alcohol (viz. methanol and ethanol) with water molecules are quite common. But, due to the presence of bulky groups in higher alcohol (viz. propanol, butanol and pentanol etc.) and their isomers, the hydrogen bonding interactions between alcohol and water molecules is significantly different. In alcohol-water heterodimer complexes, water plays an important role in the stability of such a system, alcohol will be interacting with water molecules either as proton donor or proton acceptor mode. The aim of this study is to understand the Hydrogen Bonding Interaction and Structural Change in Some Aliphatic Alcohol-Water Complexes. We have studied the hydrogen bonding interactions between some aliphatic alcohol-water complexes by computational methods. All the models were constructed by using GaussView 5.0. The interaction energy (IE) and natural bond orbital (NBO) calculations for some common aliphatic alcohol-water complexes (e.g. methanol, ethanol, propanol, butanol and pentanol) and their isomers are computed by using the MP4 method. All alcohol-water complexes can form hydrogen bonds either through proton accepting or proton donor mode of interaction. Calculation of the interaction energy of such complexes reveals that the proton acceptor (RHO—H2O) hydrogen bonding mode is always more favorable than that of the proton donor (ROH—H2O) mode of interaction.